Exploring Quizizz-based learning media for teaching maritime English vocabulary: A needs analysis for marine engineering students - Iryanti, Heni Dwi; Hidayati , Diyah Nur; Tyas , Estu Ning; Amurao, Jordan M. (Universitas Sarjanawiyata Tamansiswa, 2024)
Effective communication in Maritime English is essential for marine engineers to manage systems and ensure safety. However, the technical nature of Maritime English and diverse learner backgrounds present challenges for vocabulary acquisition. This study employs a needs analysis framework to investigate vocabulary gaps and learning preferences among 40 marine engineering students. Using questionnaires and interviews, the study identifies key challenges, including limited exposure to technical terms and difficulties with pronunciation, as well as a strong preference for interactive, gamified learning tools. Findings indicate that 75% of students find Quizizz-based platforms effective for improving vocabulary comprehension, with features such as real-time feedback and scenario-based exercises enhancing retention and engagement. Despite these benefits, 33% reported difficulties accessing tailored resources, highlighting the need for more customized materials. The study concludes that Quizizz-based tools can address learners' specific vocabulary needs and support skill development through adaptive, technology-enhanced learning strategies. These findings emphasize integrating interactive methods and contextual resources into Maritime English curricula to improve vocabulary acquisition and professional readiness.